PELAFALAN DAN PENGENALAN KOSAKATA PADA PEMELAJAR BIPA DI DALAM TES KEMAHIRAN BERBICARA - Rosida Erowati; Neneng Nurjanah (Dialektika: Jurnal Bahasa, Sastra, dan Pendidikan Bahasa dan Sastra Indonesia, 2020)
Abstract: The speaking skills of BIPA 1 learners include the ability to pronounce Indonesian phonemes accurately. The accuracy of phoneme pronunciation is not only intended for fluency in speaking, but so that students are able to distinguish the meaning of words. By utilizing a qualitative descriptive approach, this study aims to describe the pronunciation of BIPA learners in Egypt in a speaking ability test. This pronunciation description indicates the ability of BIPA learners to recognize vocabulary, the meaning of words, as well as the difficulty of pronunciation in tests of speaking ability. The results of this study indicate that beginner BIPA learners in Egypt have difficulty at the phonological level, namely the phonetic articulation of consonant sounds / b /, / p /, / ŋ /, / ɲ /, / k /, / ʔ / and consistently having difficulty to map sound / b / to / p /. In addition, it tends to double the sound / ŋ / with / ɡ /, also avoiding the sound / ɲ /.